Multi-criteria decision-making for solving transport sustainability issues: an overview - Šikšnelytė-Butkienė, Indrė; Štreimikienė, Dalia; Baležentis, Tomas; Agnusdei, Leonardo (Transport, 2024)
With the recognition of the impact of the transport sector on climate change and human health, decision-makers are under the pressure to shape the transport sector in a more sustainable way, considering more sustainable options and technologies. Besides that, it is also important to ensure such aspects as affordability, security, reliability and convenience of transport services and the effective functioning of the whole system. Therefore, transport-related policy actions require not only an economic point of view, but also environmental and social actions. The article aims to overview the application of Multi-Criteria Decision-Making (MCDM) techniques for solving sustainability issues in the transport sector and to provide the main insights for methods and sustainability criteria selection. The Search, Appraisal, Synthesis and Analysis (SALSA) framework and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement were applied as the basis for the research. The detailed content analysis of studies is arranged according to the application areas and the methods applied. In order to increase the applicability of the performed analysis and to simplify the decision-making for further studies, the thematic areas for criteria selection are proposed, the most popular MCDM techniques alongside their advantages and disadvantages are briefly discussed.